2015
DOI: 10.1007/s13277-015-4579-4
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of hSNF2H in glioma promotes cell proliferation, invasion, and chemoresistance through its interaction with Rsf-1

Abstract: hSNF2H partners with Rsf-1 to compose the Rsf complex to regulate gene expression. Recent studies indicated that hSNF2H was overexpressed in several human cancers. However, its expression pattern and biological mechanism in glioma remain unexplored. In this study, we found that hSNF2H was overexpressed in 32 % of glioma specimens. hSNF2H overexpression correlated with advanced tumor grade (p = 0.0338) and Rsf-1 positivity in glioma tissues (p = 0.016). Small interfering RNA (siRNA) knockdown was performed in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 26 publications
4
20
0
Order By: Relevance
“…The results, suggesting that high RSF1 expression indicates a poor prognosis of RCC, are consistent with data in ovarian, prostate and hepatocellular cancer (17,18,21). The results may be explained by previous studies demonstrating that RSF1 promotes tumor cell proliferation and invasion (10,13,14,16). All of these results together suggest that RSF1 is an important oncogene in RCC.…”
Section: Event-free Survivalsupporting
confidence: 90%
See 2 more Smart Citations
“…The results, suggesting that high RSF1 expression indicates a poor prognosis of RCC, are consistent with data in ovarian, prostate and hepatocellular cancer (17,18,21). The results may be explained by previous studies demonstrating that RSF1 promotes tumor cell proliferation and invasion (10,13,14,16). All of these results together suggest that RSF1 is an important oncogene in RCC.…”
Section: Event-free Survivalsupporting
confidence: 90%
“…Davidson et al indicated that the compared with low expression of RSF1, overexpression and amplification of RSF1 predicted a decreased survival in patients with ovarian cancer (21), similar to Erb-B2 receptor tyrosine kinase 2 in breast cancer (27) and MYCN proto-oncogene, BHLH transcription factor in neuroblastoma (28). It is plausible that RSF1 gene amplification and overexpression in tumor cells disrupts the homeostatic kinetics in the chromatin remodeling machinery and alters gene regulation, consequently facilitating tumorigenesis (10,29,30).…”
Section: Event-free Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well defined that Rsf-1 contributes to chemoresistance in many cancers through activation of the NF-κB pathway [18, 19, 23, 25]. Rsf-1 knockout decreased the protein levels of p-P65, BcL2, CFLAR, and XIAP in H1299 and H460 cells, confirming that Rsf-1 regulates the activation of NF-κB and the expression of the genes downstream of NF-κB complex [23, 25].…”
Section: Discussionmentioning
confidence: 83%
“…Rsf-1 knockout decreased the protein levels of p-P65, BcL2, CFLAR, and XIAP in H1299 and H460 cells, confirming that Rsf-1 regulates the activation of NF-κB and the expression of the genes downstream of NF-κB complex [23, 25]. Inhibition of the NF-κB pathway by helenalin decreased the protein levels of p-P65, BcL2, CFLAR, and XIAP in these cells without altering Rsf-1 protein levels, suggesting that Rsf-1 acts on the NF-κB pathway at a point no further downstream from the site of helenalin inhibition.…”
Section: Discussionmentioning
confidence: 94%